2013
DOI: 10.1186/gb-2013-14-1-401
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of the important oilseed crop Sesamum indicumL

Abstract: The Sesame Genome Working Group (SGWG) has been formed to sequence and assemble the sesame (Sesamum indicum L.) genome. The status of this project and our planned analyses are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 64 publications
(53 reference statements)
2
96
0
1
Order By: Relevance
“…The published sesame genome sequence (Zhang et al, 2013) was used to identify candidate genes that are known to function in other plants in the signal transduction pathways in response to abiotic as well as biotic stress, some of them possibly working as cross-talk factors. To check whether overexpression of SindOLP in sesame results in activation of phytohormone defense signaling, transcriptional profiles of the selected genes that function in the two pathways were studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The published sesame genome sequence (Zhang et al, 2013) was used to identify candidate genes that are known to function in other plants in the signal transduction pathways in response to abiotic as well as biotic stress, some of them possibly working as cross-talk factors. To check whether overexpression of SindOLP in sesame results in activation of phytohormone defense signaling, transcriptional profiles of the selected genes that function in the two pathways were studied.…”
Section: Resultsmentioning
confidence: 99%
“…These sequences were used to find corresponding genes in sesame from the sesame genome sequence (Zhang et al, 2013). The details of the work are given in Results Section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further the data would be useful in identifying parents for heterosis breeding, conservation, and genetic improvement for yield and other desirable traits in sesame. The sesame genome sequence recently studied by Zhang et al (2013b) has provided and opened up new challenges for the present scientists to improve the crop efficiently at each and every level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results indicated that no more than 8% lines among 2210 Chinese and foreign sesame germplasm resources presented the high resistance to Fos in artificial SFW nursery (data not published). The narrow genetic basis in sesame germplasm resources suggests that improving the sesame resistance level would be unlikely to be solved in the near future (Zhang et al , 2013. Till now, the FW resistance heritability and molecular mechanism analyses are not performed intensively in sesame.…”
mentioning
confidence: 99%